Delta Urbanism, Premises: Editorial - Bacchin, Taneha K; Hooimeijer, Fransje; Kothuis, Baukje Bee (Journal of Delta Urbanism, 2020)
The title of this journal is the offspring of Han Meyer who started the interdisciplinary research movement Delta Urbanism about 25 years ago. The two words describe the concept that brings focus on an integrative and interdisciplinary approach in the planning, designing and engineering of urbanised deltas –fragile and highly dynamic landscapes at sea, in deltas, and in estuaries– facing extreme challenges from competing claims and interests. As discourse, it investigates the possibilities to combine flood resilience, soil regeneration and water management strategies with urban design, landscape architecture and spatial planning. Finally, as practice, it has the objective to improve spatial form, function, and performance and innovate urban systems in urban and metropolitan delta and coastal regions. The urgency for this novel approach is seen in the quest for a new dynamic equilibrium between urban growth, port- development, agriculture, environmental and ecological qualities, flood-defence systems and fresh-water supply. Delta Urbanism, as a field of interest and action, positions itself in this search of a new modernity: planning, designing and engineering the co-existence and equity between different forms of life and inhabitation and their reciprocity within the natural environment as a whole.